2013
DOI: 10.3892/ijmm.2013.1351
|View full text |Cite
|
Sign up to set email alerts
|

Dual PI3K/mTOR inhibitor NVP-BEZ235-induced apoptosis of hepatocellular carcinoma cell lines is enhanced by inhibitors of autophagy

Abstract: Dysregulation of the phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling has been found in several types of human cancer, including hepatocellular carcinoma (HCC). NVP-BEZ235 is a novel, orally bioavailable dual PI3K/mTOR inhibitor that has exhibited promising activity against HCC in preclinical models. Autophagy is a cellular lysosomal degradation pathway essential for the regulation of cell survival and death to maintain homeostasis. This process is negatively regulated by mTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 32 publications
5
35
0
Order By: Relevance
“…In addition, inhibition of the PI3K/AKT/mTOR signaling pathway can result in the induction of autophagy [22]. Some studies have shown that inhibition of autophagy might overcome the therapeutic resistance to PI3K/AKT/mTOR signaling inhibitors in some types of tumors [3941]. Similar results were also observed in our study, which showed that addition of the autophagy inhibitor CQ enhanced matrine-induced cell apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, inhibition of the PI3K/AKT/mTOR signaling pathway can result in the induction of autophagy [22]. Some studies have shown that inhibition of autophagy might overcome the therapeutic resistance to PI3K/AKT/mTOR signaling inhibitors in some types of tumors [3941]. Similar results were also observed in our study, which showed that addition of the autophagy inhibitor CQ enhanced matrine-induced cell apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…Akt activates mTOR by phosphorylating Ser2448 sites of mTOR to enhance the efficiency of mRNA translation, thereby increasing the expression of proteins associated with cell growth and differentiation, and accelerating tumorigenesis (20). The present study revealed that silybin treatment reduced the protein levels of p-mTOR in U266 cells in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 48%
“…Chang et al (24) reported that dual phosphoinositide 3-kinase/mTOR inhibitor NVP-BEZ235-induced apoptosis of hepatocellular carcinoma cell lines was enhanced by inhibition of autophagy. In the present study, it was observed that knockdown of STMN1 led to upregulation of mTOR signaling, which additionally inhibited autophagy.…”
Section: Discussionmentioning
confidence: 99%